2011
DOI: 10.1002/icd.742
|View full text |Cite
|
Sign up to set email alerts
|

Does Children's Colour Use Reflect the Emotional Content of their Drawings?

Abstract: When children draw in clinical contexts, clinicians sometimes rely on children's colour use to make inferences about their emotional reaction to the subject of the drawing. Here, we examined whether children use colour to portray emotion in their drawings. In Experiment 1, children indicated their colour preferences and then coloured in outlines of figures characterized as nasty or nice. Children also drew complex, multi‐coloured pictures about their own happy or sad experiences. In Experiment 2, hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 69 publications
0
21
0
1
Order By: Relevance
“…The projective approach examines features in children's drawings for emotional meaning (Koppitz, , ), such as small figure size representing fear; this has been found to be unreliable as indicators of emotion leading for calls of extreme caution when projecting meaning into children's drawings (Burkitt, ; Crawford, Gross, Patterson, & Hayne, ; Lilienfeld, Wood, & Garb, ; Strange, Hoynck Van Papendrecht, Crawford, Candel, & Hayne, ; Woolford et al ., ). The present study follows an approach which investigates how children alter drawing strategies when provided with contrasting emotional characterizations of topics (Burkitt, ; Jolley, Fenn, & Jones, ; Picard & Gauthier, ; Picard et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The projective approach examines features in children's drawings for emotional meaning (Koppitz, , ), such as small figure size representing fear; this has been found to be unreliable as indicators of emotion leading for calls of extreme caution when projecting meaning into children's drawings (Burkitt, ; Crawford, Gross, Patterson, & Hayne, ; Lilienfeld, Wood, & Garb, ; Strange, Hoynck Van Papendrecht, Crawford, Candel, & Hayne, ; Woolford et al ., ). The present study follows an approach which investigates how children alter drawing strategies when provided with contrasting emotional characterizations of topics (Burkitt, ; Jolley, Fenn, & Jones, ; Picard & Gauthier, ; Picard et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…18(p84) The red color of the tree may indicate the discomfort Victor felt, but red can also be a color a child likes. 20 The last drawing shows 2 dragons with wings. These findings show a similarity to another report, where a dying child saw her disease as a monster, a being that could be viewed as representing the fearsome and destructive nature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, bright colours correlated with the absence of depression and the use of darker colours with the presence of depression. Many authors have warned against reading too much into the colours that children use when drawing pictures (Crawford et al, 2012;Dolidze et al, 2013;Alter-Muri and Vazzano, 2014). They also found that children tend to use their best or favourite colour more when drawing pictures.…”
Section: Discussionmentioning
confidence: 99%
“…accuracy of interpreting child drawings, but it is still among the 10 most used psychological assessment measures worldwide (Farokhi and Hashemi, 2011;Willcock et al, 2011;Crawford et al, 2012). Although it is not possible to make a specific diagnosis from drawings, it can be a strong indication of emotional distress and is therefore a good screening tool (Skybo et al, 2007).…”
mentioning
confidence: 99%